2022
DOI: 10.3389/fgene.2022.812411
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Metabolome Integration Provides New Insights Into the Regulatory Networks of Tibetan Pig Alveolar Type II Epithelial Cells in Response to Hypoxia

Abstract: Tibetan pigs show a widespread distribution in plateau environments and exhibit striking physiological and phenotypic differences from others pigs for adaptation to hypoxic conditions. However, the regulation of mRNAs and metabolites as well as their functions in the alveolar type II epithelial (ATII) cells of Tibetan pigs remain undefined. Herein, we carried out integrated metabolomic and transcriptomic profiling of ATII cells between Tibetan pigs and Landrace pigs across environments with different oxygen le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Accordingly, in this study Meishan piglets were used as an experimental model to compare how differences in rearing conditions (NC vs. ASF) would impact immune status. Many other metabolomic and transcriptomic studies of pigs exposed to environmental stressors have been published to date ( 11 , 30 ). This study, however, is the first to our knowledge to conduct an integrated metabolomic and transcriptomic analysis in Meishan pigs, highlighting phenotypes that are dependent on rearing conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, in this study Meishan piglets were used as an experimental model to compare how differences in rearing conditions (NC vs. ASF) would impact immune status. Many other metabolomic and transcriptomic studies of pigs exposed to environmental stressors have been published to date ( 11 , 30 ). This study, however, is the first to our knowledge to conduct an integrated metabolomic and transcriptomic analysis in Meishan pigs, highlighting phenotypes that are dependent on rearing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Raw data were processed as in a prior report ( 11 ). Briefly, Proteowizard (v 3.0.8789) converted these raw data files into the mzXML format, after which peak identification, filtration, and alignment were conducted with the R (v3.3.2) XCMS package ( 12 ) using the following settings: bw = 5, ppm = 15, peakwidth = c (5,30), mzwid = 0.01, mzdiff = 0.01, method = “centWave.” Subsequent analyses were then performed based on the m/z ratio, retention time, intensity, and positive/negative precursor ions.…”
Section: Methodsmentioning
confidence: 99%
“…A newborn Tibetan piglet was selected and slaughtered under aseptic conditions after anesthesia to collect the lung tissue. Primary ATII cells were isolated from the lungs according to the method of Yang et al [ 35 ]. Isolated ATII cells were randomly divided into two groups, namely the control group (21% O 2 , normoxia) and experimental group (2% O 2 , hypoxia).…”
Section: Methodsmentioning
confidence: 99%
“… 14 Analysis of the combined transcriptome and metabolome provides the information to interpret key molecules from genes to phenotypes. In pigs, some combined transcriptome and metabolome studies for important economic traits or drug reactions have been reported, such as feed efficiency, 15 hypoxia-related signature, 16 and the responses of pigs orally inoculated with amoxicillin solution, 17 while studies on metabolites in various stages of pregnancy are still quite a few. Therefore, characterizing the molecular mechanisms of the reproduction and lactation process of pigs based on the transcriptome and metabolome data will be very necessary and can be a useful model for human pregnancy disorders.…”
Section: Introductionmentioning
confidence: 99%